Kebiasaan Mengkonsumsi Jajanan Kariogenik Sebagai Penyebab Karies Gigi Pada Anak Di Madrasah Diniyah Islamiyah Muhammadiyah Kindaung Banjarmasin - Eddy Rahman; M. Bahrul Ilmi; Khairul Anam (HB PRESS, 2018)
Dental caries is a hole that forms in the teeth, which results from a process that gradually dissolves the enamel (the hard outer surface of the tooth) and continues to develop into the inside of the tooth.Based on preliminary studies conducted by examining students at the Muhammadiyah Islamic Boarding School (MDIM) Banjarmasin as many as 33 people, 20 of them had dental caries. The purpose of this study was to determine the habits of consuming cariogenic food as a cause of dental caries in MDIM Banjarmasin. The type of research used in this study is quantitative research with an analytical survey approach. The population in this study were all fourth and fifth grade students in MDIM Banjarmasin, 144 students. Based on statistical tests with significance value (a) 0.05, confidence value 95% & obtained p-value = 0.022. P-value is smaller than the significance value (α) 0.05, this means that there is statistically a relationship between the habits of consuming cariogenic food as a cause of dental caries in children in MDIM Banjarmasin. It is expected that the UKGS (School Dental Health Service) program will be intensified by providing health services in schools.